First-pass intubation success rate during rapid sequence induction of prehospital anaesthesia by physicians versus paramedics. (December 2015) - Peters, Joost; van Wageningen, Bas; Hendriks, Ilze; Eijk, Ruud; Edwards, Michael; Hoogerwerf, Nico; Biert, Jan
Abstract : Introduction: Endotracheal intubation is a frequently performed procedure for securing the airway in critically injured or ill patients. Performing prehospital intubation may be challenging and intubation skills vary. We reviewed the first-attempt tracheal intubation success rate in a Dutch prehospital setting. Patients and methods: We studied our database for all intubations performed by helicopter emergency medical services (HEMS) physicians, HEMS nurse and ambulance paramedics under HEMS supervision between January 2007 and July 2012. The primary outcome was success rate, number of intubation attempts and alternative airway procedures. Results: In all, 1399 patients were in need of a secured airway. In 571 (40.8%) of these cases, ambulance paramedics made a first intubation attempt under HEMS supervision. If necessary, rapid sequence induction medication was administered. In comparable patient groups, the first intubation success rate was significantly lower in ambulance paramedics compared with helicopter physicians (46.4 vs. 84.5%, P <0.0001). The overall physician intubation success rate was 98.4% after one or more intubation attempts. In 19 cases, a surgical airway was created and in three cases an alternative ventilation method was used. Conclusion: Prehospital intubations had a significantly higher success rate when performed by helicopter physicians. We promote a low threshold for HEMS deployment in cases of a potentially compromised airway.